2010
DOI: 10.1002/mds.23441
|View full text |Cite
|
Sign up to set email alerts
|

Rotigotine effects on early morning motor function and sleep in Parkinson's disease: A double‐blind, randomized, placebo‐controlled study (RECOVER)

Abstract: In a multinational, double-blind, placebo-controlled trial (NCT00474058), 287 subjects with Parkinson's disease (PD) and unsatisfactory early-morning motor symptom control were randomized 2:1 to receive rotigotine (2–16 mg/24 hr [n = 190]) or placebo (n = 97). Treatment was titrated to optimal dose over 1–8 weeks with subsequent dose maintenance for 4 weeks. Early-morning motor function and nocturnal sleep disturbance were assessed as coprimary efficacy endpoints using the Unified Parkinson's Disease Rating Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
270
5
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(304 citation statements)
references
References 28 publications
22
270
5
7
Order By: Relevance
“…Both were closely related to the disease per se of PD. Some researchers also regrouped different items into special domains to explore aspects of nocturnal disturbance of specific interest (Ray Chaudhuri et al., 2012; Trenkwalder et al., 2011). Therefore, we categorized individual item into five domains to illustrate the different characteristics in the 15 items, and to correlate each domain with nighttime and daytime sleep problems (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Both were closely related to the disease per se of PD. Some researchers also regrouped different items into special domains to explore aspects of nocturnal disturbance of specific interest (Ray Chaudhuri et al., 2012; Trenkwalder et al., 2011). Therefore, we categorized individual item into five domains to illustrate the different characteristics in the 15 items, and to correlate each domain with nighttime and daytime sleep problems (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Trenkwalder et al performed a placebocontrolled, double-blind, multinational trial and found that rotigotine could significantly improve the modified Parkinson's Disease Sleep Scale (PDSS-2) and UPDRS Part III scores in comparison with the placebo 10 . Patients, who received the maximum dose of rotigotine, exhibited a significantly improved UPDRS Part I, II and III scores, indicating that rotigotine is effective, safe and well-tolerated for the treating patients with early-stage PD 25,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Nicholas et al also reported higher incidence of AEs, including dry mouth, application-site reactions, dyskinesia and nausea, in the rotigotine group (8 mg/24 h) than in the placebo group 26 . Furthermore, Trenkwalder et al found that the most common AEs were nausea (rotigotine, 21% and placebo, 9%), dizziness (rotigotine 10% and placebo, 6%) and applicationsite reactions (rotigotine, 15% and placebo, 4%) 10 . These results indicate that rotigotine has higher incidence of AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some evidence supports the efficacy of certain treatments for depression, dementia, psychosis, constipation, orthostatic hypotension and sialorrhea, there is insufficient evidence for efficacious treatments for other important non-motor symptoms that certainly contribute to poor quality of life, such as neurogenic bladder disturbance, erectile dysfunction, fatigue, insomnia, apathy, anxiety and excessive daytime sleepiness [60,63]. The emergence of recent controlled trials concentrated on key non-motor issues such as Parkinson associated pain [64] or sleep [65] is highly encouraging. Nevertheless, the broad spectrum of NMS in PD clearly highlight the need for developing non-dopaminergic therapies that target the nondopaminergic degeneration in PD.…”
Section: Management Of Non-motor Complicationsmentioning
confidence: 99%